Mastering Lymphatic Microsurgery: A New Training Model in Living Tissue. Issue 3 (September 2017) - Campisi, Corrado Cesare; Jiga, Lucian P.; Ryan, Melissa; di Summa, Pietro G.; Campisi, Corradino; Ionac, Mihai
Abstract : Background: Advanced microsurgical techniques have emerged as a promising approach for the treatment of lymphedema, but achieving international standards is limited by a scarcity of adequate training models. The purpose of this report is to describe our in vivo porcine training model for microsurgery. Study Design: Five female common-breed pigs ( Sus scrofa domesticus ) weighing 20 to 28 kg were placed under general anesthesia, and blue patent violet dye was injected to highlight lymphatic structures and prepare the pigs for anatomical exploration and microsurgery. The number and type of patent anastomoses achieved and lymph node flaps created and any anatomical differences between porcine and human vessels were noted, in light of evaluating the use of pigs as a training model for microsurgery in living tissue. Results: Multiple lymphatic-venous anastomoses were created at the site of a single incision made at the subinguinal region, running medial and parallel to the saphenous vessels. Ten multiple lymphatic-venous anastomoses were created in total, and all were demonstrated to be patent. Four lymph node flaps were prepared for lymph node transfer. The superficial lymphatic collector system in the caudal limb of the pig was identified and described with particular reference to the superficial, medial (dominant), and lateral branches along the saphenous vein and its accessory. Conclusions: The authors present a safe and adaptable in vivo experimental microsurgical porcine model that provides the opportunity to practice several advanced lymphatic microsurgical techniques in the same animal. The ideal lymph node transfer training model can be developed from this anatomical detail, giving the opportunity to use it for artery-to-artery anastomoses, vein-to-vein anastomoses, and lymphatic-to-lymphatic anastomoses.